Why Socio-metabolic Studies are Central to Ecological Economics - Simron J Singh; Simran Talwar; Megha Shenoy (Ecology, Economy and Society – The INSEE Journal, 2021)
Global material extraction has tripled since the 1970s, with more than 100 billion tonnes of materials entering the world economy each year. Only 8.6% of this is recycled, while 61% ends up as waste and emissions that is the leading cause of global warming, and large-scale pollution of land, rivers, and oceans. This paper introduces Socio-metabolic Research (SMR) and demonstrates its relevance for ecological economics scholarship in India. SMR is a research framework for studying the biophysical stocks and flows of material and energy associated with societal production and consumption. SMR is widely conducted in Europe, US, and China. In India, it is still at an infant stage. In this paper, we review pioneering efforts of SMR in India, and make the case for advancing the field in the sub-continent. The crucial question is whether India can source materials and energy necessary for human development in a sustainable manner.